رقابة الامتناع كآلية للرقابة على دستورية القوانين في النظام السعودي: دراسة مقارنة - شحاته، جهاد مغاوري Shehatah, Jehad Maghawri (جامعة الأزهر - کلية الدراسات الإسلامية والعربية للبنات بالإسكندرية, 2018)
في هذا البحث آلية الرقابة على دستورية القوانين في النظام السعودي، دراسة مقارنة، وكانت مشكلة البحث تتلخص في إلقاء الضوء على آلية الرقابة على دستورية القوانين في النظام السعودي، وقد حاولت من خلال هذا البحث الإجابة على التساؤلات الفرعية التالية، 1) ما هو مفهوم الرقابة الدستورية وخصائصها، 2) ما هي أنواع الرقابة على دستورية القوانين والفرق بينهما. 3) ما هي آلية الرقابة الدستورية في النظام السعودي. كما يتبين لنا أن الرقابة الدستورية تعني التحقق من مدى مطابقة القوانين للقواعد الدستورية تحقيقا لمبدأ سمو الدستور، وتم إلقاء الضوء على أهمية الرقابة على دستورية القوانين، وخصائص الرقابة على دستورية القوانين، وأنواع الرقابة على دستورية القوانين في النظم المقارنة، وتبين لنا أنها إما أن تكون رقابة سياسية، تقوم بها جهة سياسية، وإما أن تكون رقابة قضائية تقوم بها جهة قضائية، وتلك الجهة القضائية قد تكون رقابة إلغاء وفيها يقوم القاضي المختص بإلغاء النص القانوني المخالف للدستور، وإما أن تكون رقابة امتناع، وفيها تقتصر سلطة القاضي على مجرد الامتناع عن تطبيق النص القانوني المخالف للدستور، كما ألقينا الضوء على وسائل الرقابة القضائية في النظم المقارنة، ثم انتقلنا إلى بيان الرقابة الدستورية في النظام السعودي، وتبين لنا أنه لا يوجد نص صريح في النظام الأساسي للحكم السعودي يقرر الرقابة الدستورية، إنما تستفاد الرقابة من النصوص القانونية في النظام القانوني.
In this research, the mechanism of control over the constitutionality of laws in the Saudi system is a comparative study. The problem of research is to shed light on the mechanism of monitoring the constitutionality of laws in the Saudi system. In this research, I tried to answer the following sub-questions: (2) What are the types of control over the constitutionality of laws and the difference between them (3) What is the mechanism of constitutional oversight in the Saudi system. As we find out that constitutional oversight means verifying the extent to which the laws comply with the constitutional rules in accordance with the principle of the supremacy of the constitution, and the importance of monitoring the constitutionality of laws, the characteristics of control over the constitutionality of laws, and the types of control over the constitutionality of laws in comparative systems. Political control, carried out by a political party, or judicial control by a judicial body, and that judicial body may be a single court, and may be all courts of different degrees and types. As may be censorship cancellation and in which the competent judge to cancel the legal text contrary to the Constitution. Or the control of abstention. In this case, the judge's authority is limited to refraining from applying the legal text that violates the constitution. The basic rule of the Saudi government determines the constitutional control, but the censorship of the legal texts in the legal system.
Keywords: الرقابة الدستورية -- دستورية القوانين -- رقابة الامتناع -- النظام السعودي